THE INFLUENCE OF RECITATION METHOD, LEARNING MOTIVATION, AND TIME MANAGEMENT ON STUDENT LEARNING INDEPENDENCE IN ECONOMIC SUBJECT - Latiful HIdayat; Lilik Sri Hariani (RADJA PUBLIKA, 2026)
Learning independence is a crucial aspect of the human resource development process in education. This study aims to explore the influence of the recitation method, learning motivation, and time management on the learning independence of students in economic subjects at MAN Kota Pasuruan. Using an explanatory research design with a quantitative approach, data were collected from 165 tenth-grade students selected through proportional random sampling. Data collection utilized Likert-scale questionnaires validated for reliability and validity. Multiple linear regression analysis was employed to test the hypotheses. The results of the simultaneous test (F-test) showed a significant influence of all three independent variables on learning independence (p < 0.001). Individually, the t-test results revealed that time management has the most dominant positive influence (coefficient 0.374), followed by the recitation method (0.289) and learning motivation (0.274). The R-square value of 0.620 indicates that these variables collectively explain 62% of the variance in student independence. These findings underscore the importance of integrating structured assignments, psychological encouragement, and time-management skills to foster independent learners.